2015
DOI: 10.5713/ajas.14.0757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Saccharomyces cerevisiae</i> Supplementation and Anhydrous Ammonia Treatment of Wheat Straw on <i>In-situ</i> Degradability and, Rumen Fermentation and Growth Performance of Yearling Lambs

Abstract: The effects of Saccharomyces cerevisiae supplementation (6.6×108 cfu) and anhydrous ammonia treatment (3%) of wheat straw (WS) were investigated on in-situ dry matter (DM) degradability, and on rumen fermentation and growth performance of lambs. Rumen-fistulated Menemen sheep fed a diet with and without live yeast were used to assess the DM degradability characteristics of WS and ammonia-treated wheat straw (WSNH3). Twenty-six yearling Menemen male lambs were fed in four groups. Lambs of control group (WS) rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…In the current study, ADFI, NWG, ADG and FCR were improved when the lambs were fed ammoniated maize stover at lower levels (up to 20%) compared with the control and AMS40 diets. This is could possibility be due to an improved degradability of water-insoluble fraction, voluntary ME intake, voluntary CP intake and ultimately growth performance in the lambs fed the ammoniated straws, as observed in other studies (Cömert et al 2015). The high growth performance data in lambs receiving diets with lower ammoniated maize stover inclusions is also consistent with the findings by Dayani et al (2011) along with Mudgal et al (2018) who reported an improved growth performance of animals receiving ammoniated roughagebased complete rations.…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, ADFI, NWG, ADG and FCR were improved when the lambs were fed ammoniated maize stover at lower levels (up to 20%) compared with the control and AMS40 diets. This is could possibility be due to an improved degradability of water-insoluble fraction, voluntary ME intake, voluntary CP intake and ultimately growth performance in the lambs fed the ammoniated straws, as observed in other studies (Cömert et al 2015). The high growth performance data in lambs receiving diets with lower ammoniated maize stover inclusions is also consistent with the findings by Dayani et al (2011) along with Mudgal et al (2018) who reported an improved growth performance of animals receiving ammoniated roughagebased complete rations.…”
Section: Discussionsupporting
confidence: 87%
“…The productive response of lambs to Saccharomyces cerevisiae supplementation varies depending on the level of yeast inclusion. Obeidat (2017) reported that 0.5 g Saccharomyces cerevisiae did not affect daily weight gain, while Cömert et al (2015) observed increases in daily weight gain with 4 g of yeast, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
“…The increase in VFA concentrations in this present study indicates enhanced microbial activity in terms of fermentation and agrees with previous findings regarding total bacteria populations [ 2 , 4 ]. The decrease in the ruminal NH 3 -N concentration seemed to be due to increased absorption of NH 3 -N into microbial proteins, probably because of the stimulation of microbial activity by S. cerevisiae [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%